You've Been Warned: Does Information About Pitfalls of Technological Toys Affect Caregiver Behavior?. Issue 1 (28th November 2022) - Hassinger‐Das, Brenna; Dore, Rebecca A.; Zosh, Jennifer M.
Abstract: Although the presence of toys in childhood has remained steady for decades, the types of toys that fill children's toy boxes have changed, especially over the last 10–15 years. Many of today's toys are marked by technological enhancements, from a shape sorter driven by a singing bear to robotic plastic animals designed to match a toddler's favorite television show. Although examining the effects of these changes is still an unexplored area, research to date suggests that there may be costs to the quality of caregiver–child interaction when using these toys together. This leads to two possibilities: (1) the design of the enhancements themselves hurt interactions; or (2) these toys can still be beneficial to interactions, but caregivers simply need to be aware of the potential pitfalls. In this study, we explore whether providing caregivers with a subtle cue about the potential negative impacts of technological toys on caregiver–child interaction affects their behavior. LAY ABSTRACT: Many of today's toys feature technological enhancements, from a shape sorter driven by a singing bear to robotic animals from a toddler's favorite television show. Research suggests that there may be costs to the quality of caregiver–child interaction when using these toys. In this study, we explore whether providing caregivers with a subtle cue about the potential negative impacts of technological toys on caregiver–child interaction affects their behavior.